Challenges in Translating the Lyrics of the Song “Bojo Galak” by Pendhoza from Javanese into Indonesian: Tantangan Menerjemahkan Lirik Lagu “Bojo Galak” Karya Pendhoza dari Bahasa Jawa ke Bahasa Indonesia - Nugroho, Agus Digdo Nugroho (Jurnal Penerjemahan, 2025)
Translating dangdut koplo song lyrics presents its own challenges. Gender bias, red-herring fallacy, unclear meanings, and inequivalent popular Javanese terminologies to target language present challenges. For example, the lyrics of Pendhoza's song "Bojo Galak" have been translated numerous times, but there is no proof that they have met the requirements of equivalence, readability, and acceptability. The methodology used for this analysis is a function-oriented research with a descriptive approach. Challenges in translating popular Javanese dangdut koplo songs include the difficulty in finding words that meet equivalence, readability, and acceptability. Translators fall into etymological fallacies and red herring fallacies. Translators fail to fully translate song lyrics, despite their unified, interconnected, and flowing whole. Translators must be able to overcome the phenomenon of culture-specific concepts, develop sentence structure skills, and manage the challenge of managing what are called the source language concept, which is not lexicalized in the target language, the source language word is semantically complex, differs in physical or interpersonal perspective, and has differences in expressive meaning.